2012
DOI: 10.1080/10509674.2012.702715
|View full text |Cite
|
Sign up to set email alerts
|

HIV/STI Risk Behavior of Drug Court Participants

Abstract: Drug abusing offenders have high rates of HIV and other sexually transmitted infections (STI). To date, the HIV/STI prevention needs of offenders in drug court programs have been ignored. This multi-method study employed interviews to assess drug court professionals’ perceptions of the need for an HIV risk reduction intervention to be integrated into the services provided to drug court participants. Then, surveys were completed by 235 drug court participants to assess whether their sexual risk behaviors affirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Adult Drug Court (ADC) Best Practice Standards encourage interventions to reduce HIV among ADC enrollees, yet very few ADCs address HIV prevention [ 9 , 10 , 13 ]. HIV prevention education and support for HIV testing are far from universal in these high-risk populations [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adult Drug Court (ADC) Best Practice Standards encourage interventions to reduce HIV among ADC enrollees, yet very few ADCs address HIV prevention [ 9 , 10 , 13 ]. HIV prevention education and support for HIV testing are far from universal in these high-risk populations [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug courts and criminal justice programs serving individuals in community settings have recently received encouragement for a greater focus on HIV interventions [9,10,13]. Further, an array of venues have been proposed as useful in reaching at-risk populations, such as communitybased health offices [14][15][16]; however, embedding HIV education into the required programming may make access most effective.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Robertson, St. Lawrence, and McCluskey (2012) found that Drug Court participants perceived their risk of HIV/AIDS as low, though substance use and risky sexual behaviors are often co-occurring and synergistic. Lastly, female substance users involved with additional interventions such as case management have been shown to significantly reduce their substance use over time (Corsi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%